Antisipasi Ide Kreatif Mahasiswa Level Rigor dalam Menentukan Algoritma Benda Ruang Menggunakan Maple - Erfan Yudianto (Didaktik Matematika, 2017)
This research motivated by the desire of researchers to uncover the anticipation of student creative ideas Rigors level (accuracy) using the Maple program. The purpose of this research to analyze the anticipation of creative ideas by rigor level students (accuracy) in observing problems related to analytical geometry of space. The method used in this research is explorative qualitative research. Subject consists of three students with initials R1, R2, and R3. The results obtained that the subject of R3 tends to use the type of anticipatory analytics because they understand the problem what given well and use logical reasoning. While the subjects R1 and R2 more using the type of anticipatory explorative because it is still found trial and error activities in making algorithms of some parts of the form to be made. Students can create algorithms about what they see.